2018
DOI: 10.1002/prca.201700117
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Quantitative Proteomic Screening of Candidate Plasma Biomarkers for the Prognosis of Breast Cancer with Different Lymph Node Statuses

Abstract: The present dataset provides a list of candidate biomarkers that could be used for early differentiation diagnosis and prognosis of breast cancer with lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…SERPIND1, which was significantly up-regulated in the reactive perfusate samples, was also upregulated in node-negative Her2-positive BC patients 17 . KRT9 was significantly up-regulated in the metastatic perfusate samples; this was found to be up-regulated in node-positive Her2-positive patients previously 17 . Lobo et al found APOC3 to be up-regulated in patients with stage I/II BC (i.e.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…SERPIND1, which was significantly up-regulated in the reactive perfusate samples, was also upregulated in node-negative Her2-positive BC patients 17 . KRT9 was significantly up-regulated in the metastatic perfusate samples; this was found to be up-regulated in node-positive Her2-positive patients previously 17 . Lobo et al found APOC3 to be up-regulated in patients with stage I/II BC (i.e.…”
Section: Resultsmentioning
confidence: 86%
“…With regard to proteomics, there is little concordance between the few studies that have tried to identify biomarkers of axillary disease in human serum/plasma samples [12][13][14][15][16][17] . Similarly, human tissue studies comparing the proteomes of primary BC to matched ALN metastases have yielded disparate data [18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…The fact that we identified such a high number of bound proteins is mainly due to the extensive fractionation strategies we applied post low-abundance protein enrichment. Most proteomics studies that have employed the ProteoMiner kit with no additional fractionation report identification of ∼500–1000 proteins. ,,, …”
Section: Discussionmentioning
confidence: 99%
“…Most proteomics studies that have employed the ProteoMiner kit with no additional fractionation report identification of ∼500−1000 proteins. 16,19,20,54 While analyzing the ProteoMiner unbound fractions (flowthrough), we identified 3682 total proteins in the flowthrough, indicating that the fractionation facilitated identification of increased numbers of proteins but also demonstrated bead saturation of a very large number of proteins, which would be problematic for subsequent quantitative work. To overcome this quantification issue, it is possible that the proteins uniquely expressed in the bound fraction, but not present in the unbound fraction, could be compared in a relative quantification approach since these are not saturated.…”
Section: ■ Discussionmentioning
confidence: 99%